HUMAN DIROFILARIASIS: AN UNCOMMON CASE OF SUB CUTANEOUS INFECTION WITH DIROFILARIA REPENS WITH A BRIEF REVIEW OF LITERATURE - H., Sanjeev; M., Rajini; R., Prasad S. (Journal of Health and Allied Sciences NU, 2011)
Dirofilaria are a group of arthropod borne filarial nematodes that cause infection in wide range of domestic and wild animals. Dirofilaria repens is a common zoonotic infection in countries like Sri Lanka. Human infection with Dirofilaria repens is not widely recognized in India. Most of the documented cases of human dirofilariasis recorded in India presented with ocular infections, affecting the eyelid, periorbital region and occasionally the sub conjunctivae. Here we report a rare case of sub cutaneous dirofilariasis, which presented as a swelling at an uncommon site.
Keywords: Dirofilariasis; Dirofilaria repens; Dirofilaria tenuis